Postering Media In Teaching English To Kindergarten Students At Tk/Ra Ihya Al Ulum Universitas Islam Makassar - Mursidin, Muthmainnah; Ilmiah Mursidin, Ida; Rahmadani, Dhini (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstract: This study aims to describe the effectiveness of using poster media in the English language teaching and learning process within early childhood education settings. A qualitative descriptive method was employed, involving 18 kindergarten students as research subjects. The findings indicate that the use of posters successfully captures students' attention, enhances their active participation during the learning process, and leads to satisfactory evaluation outcomes. Instructional media such as posters not only facilitate students’ comprehension of the material but also make the learning experience more engaging and interactive. This study highlights the importance of incorporating visual media like posters to improve the quality of English language learning for young children.